Formalize Without Integrating? Land Regularization, Citizenship and Social Appropriation in the Mismatch between the Informal City and the Formal City - Godoy, Jeane Aparecida Rombi de; Benini, Sandra Medina; Silva, Allan Leon Casemiro da (National Journal of City Management, 2026)
Objective - to analyze the limits of land regularization policy in Brazil as a mechanism of urban integration, proposing the analytical category of incomplete formalization.Methodology - the article adopts a mixed critical-documentary approach, combining literature review, regulatory analysis and descriptive analysis of secondary data from official repositories, especially IBGE, Fundação João Pinheiro and IPEA.Originality/Relevance - the study addresses the theoretical gap related to post-formal situations in which territory is legally recognized but remains materially segregated and institutionally integrated only partially.Results - the findings indicate that the emphasis on individual titling, when detached from infrastructure, urban services and social participation, tends to produce selective integration and low-intensity territorial citizenship.Theoretical/Methodological Contributions - the article operationally distinguishes incomplete formalization from neighboring concepts such as precarious tolerance, precarious integration, insurgent citizenship and informality as a mode of state regulation.Social and Environmental Contributions - the study highlights the need to associate tenure security, urbanization, sanitation, mobility, residents permanence and sociospatial justice in land regularization policies.
Keywords: Urban informality; Land regularization; Incomplete formalization; Territorial citizenship; Right to the city